IMPLEMENTASI METODE QUALITY CONTROL CYCLE (QCC) UNTUK PENINGKATAN KAPASITAS PRODUKSI BODY CENTER PILLAR DI PERUSAHAAN OTOMOTIF - Attaqwa, Yusita; Sari, Nita Winda; Kusmayadi, Didi (Jurnal Teknologi Terapan, 2025)
This research was conducted at manufacturer of Toyota and Daihatsu brand cars. One of the products, the Body Center Pillar part, is the lowest productivity, where the target PPH is 50 pcs / hour, the actual PPH is 40 pcs / hour or still minus 10 pcs every hour. Necessary non valuable work that causes a high cycle time of 90 seconds, thus affecting production capacity. This study aims to determine the factors that cause Non-Valuable Work which results in a high Cycle Time of 90 seconds, which has an impact on low production capacity in line 6D-01-1 using the Quality Control Cycle (QCC) method. The subject of the study is the work process carried out by production operators where the productivity results are still low while the object of research is the measurement of process time or Cycle Time Part Body Center pillar consisting of 4M and 1E factors, namely: Machines, Materials, Methods, People, and Environment. After making some improvements of the engine factors and methods, use the Quality Control Cycle (QCC) method. Cycle Time decreased to 72 seconds so that PPH increased from 40 pcs to 50 pcs and production productivity in line 6D-01-1 increased.